PROSPECTS FOR THE INTEGRATED USE OF SLAG WASTES FROM FERROCHROME PRODUCTION FOR HEAT-RESISTANT MATERIALS - Bazhirov Tynlybek Saifutdinovich,; Protsenko Vyacheslav Sergeyevich,; Bazhirov Nurlybek Saifutdinovich,; Dauletiyarov Mukhtar Srazhevich,; Serikbayev Bolatzhan Yermahanovich,; Bazhirova Kamshat Nurlybekovna, (Academic Scientific Journal of Chemistry, 2020)
The research results of physicochemical and physicotechnical properties of slag wastes from ferrochrome production as raw materials for heat-resistant materials are presented. Chemical and mineralogical composition of slag from high-carbon ferrochrome production and slag from low-carbon ferrochrome production, as well as their constituent main crystalline phases, represented by magnesium and calcium aluminosilicates of complex composition, have been determined by physicochemical research methods. According to X-ray phase analysis, the slag from the high-carbon ferrochrome production is represented mainly by forsterite Mg2SiO4, spinel MgAl2O4, partially amorphous glass phase and admixture of calcium orthosilicate Ca2SiO4. In the slag from the low-carbon ferrochrome production, the main crystalline phase is calcium orthosilicate γ-Ca2SiO4, as well as magnesium orthosilicate forsterite Mg2SiО4. The research results of specific surface area, average particle size determination and sieve analysis have shown that the slag from the low-carbon ferrochrome production is a finely dispersed gray powder with the following characteristics: the specific surface area – 295 m2 /kg, the average particle size – 6.8 μm, the true density – 3.01 g/cm3 , the bulk density – 739 kg/m3 . The research of the physicochemical and physicotechnical properties has established that in terms of chemical, mineralogical composition and refractoriness indices, the slags from the high-carbon ferrochrome and low-carbon ferrochrome productions can be valuable raw materials for heat-resistant materials.